PSXI-20 Heat stress induces proteomic changes in the liver and mammary tissue of dairy cows independent of feed intake: an iTRAQ study. - Ma, L (J Anim Sci, 2018)
Heat stress has been shown to decrease milk yield and alter milk composition in dairy cows. Reduced feed intake partially accounts for some of the changes observed during heat stress but metabolic changes in the mammary tissue and liver associated with milk synthesis have not been thoroughly evaluated. In this study, four lactating Chinese Holstein cows were randomly assigned into a two-treatment crossover design with a 9 days experimental period and a 30 days thermal neutral wash out period in each treatment. Dry matter intake was measured individually once daily. The two heat-stressed cows were individually housed in a climatic chamber and fed ad libitum with the temperatures ranging from 32 to 36°C, with 55% humidity, and 12 h light and dark cycles. The other two pair-fed cows were also individually housed in a climatic chamber under thermal neutral conditions, but fed matching the feed intake of the heat-stressed cows. Mammary and liver tissue needle biopsies were collected from individual cows on the last day of each environmental period. Changes of protein abundance in the mammary tissue and liver were investigated using the iTRAQ proteomic approach. Most of the differentially expressed proteins from mammary tissue and liver between heat-stressed and pair-fed cows were involved in GO category of protein metabolic process. Pathway analysis indicated that differentially expressed proteins production of pyruvate (P=0.011), glyoxylate and dicarboxylate (P=0.048) in mammary tissue was increased, while those in the liver involved in oxidative phosphorylation (P=0.004) and antigen processing and presentation (P=0.043) pathways. HSP 90-beta and HSP 90-alpha as heat shock proteins directly interact with each other and were considered as central “hubs” in the protein interaction network. These findings provide new insights into protein biosynthesis within liver and mammary tissues that may contribute to changes in milk protein composition occurring in heat-stressed dairy cows. Key Words: